"A clue in a labyrinth:" The medico-chemistry of the stone in the life of Edward Darrell Smith. (November 2020) - Driggers, Edward A
This article will argue that Edward Darrell Smith engaged in chemical analysis in order to broaden his understanding of the body, particularly stones, in a humoral framework. At the time, Antoine Lavoisier's chemical innovations were exciting the medical world, and Lavoisier himself was pursuing medical questions in his chemical research. Medical students from Philadelphia to Charleston were writing dissertations on the different types of stones and concretions found in the body. Smith practiced medicine in a world in which the remedy for the stone was compelling and a long awaited discovery. By examining Edward Darrell Smith's biography, we can get a vista into this world.